2021
DOI: 10.1177/1759720x211040300
|View full text |Cite
|
Sign up to set email alerts
|

Soluble biological markers in osteoarthritis

Abstract: In recent years, markers research has focused on the structural components of cartilage matrix. Specifically, a second generation of degradation markers has been developed against type II collagen neoepitopes generated by specific enzymes. A particular effort has been made to measure the degradation of minor collagens III and X of the cartilage matrix. However, because clinical data, including longitudinal controlled studies, are very scarce, it remains unclear whether they will be useful as an alternative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 166 publications
1
12
0
Order By: Relevance
“…In the field of biomarker research, cartilage markers have been the subject of comprehensive and in-depth studies. In line with the findings of previous studies [ 12 , 37 ], our study reaffirmed the elevation of promising OA biomarkers, namely, pHA and uCTX-II, in severe knee OA. Additionally, we observed increased urinary levels of COMP, HA, MMP-1, and MMP-3 in severe knee OA patients compared with controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the field of biomarker research, cartilage markers have been the subject of comprehensive and in-depth studies. In line with the findings of previous studies [ 12 , 37 ], our study reaffirmed the elevation of promising OA biomarkers, namely, pHA and uCTX-II, in severe knee OA. Additionally, we observed increased urinary levels of COMP, HA, MMP-1, and MMP-3 in severe knee OA patients compared with controls.…”
Section: Discussionsupporting
confidence: 92%
“…Joint synovial fluid (SF) contains substances related to OA pathophysiology, including inflammatory mediators, cartilage-degrading enzymes, and cartilage-derived products; thus, it occupies an important position in biomarker research for OA. However, limitations in developing and clinically applying SF-based biomarkers exist due to the invasiveness of sample collection, variations in the presence of SF, and the skilled techniques required for collection [ 12 ]. Recently, blood or urine, which can be collected by a less invasive route, have been applied in biomarker research as a surrogate matrix for SF.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that studies based on the expression and translation levels of these four hub genes in synovial fluid, blood, and urine possess clinical importance, and that changes in these candidate biomarkers may play a vital role in the detection of OA. 41 To further explore the potential molecular mechanisms of the four key genes in OA, we constructed a PPI network based on these crucial genes through the GeneMANIA database. Annotation of the gene functions through KEGG and GO analyses revealed that the neurotrophin signalling pathway, the thyroid hormone signalling pathway, the PI3K-Akt signalling pathway, thyroid hormone generation, the positive regulation of apoptotic signalling pathway, and the stress-activated mitogen-activated protein kinase (MAPK) cascade were the most important functional categories.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, inflammation is still an important contributor to the development and progression of OA, even in the early stages. 18 Structural alterations in the OA-inflicted joint are hypothesized to be linked, at least in part, to multiple proinflammatory cytokines. 57 The role of inflammatory mediators in human OA has been extensively reviewed.…”
Section: Emerging Molecular Biomarkersmentioning
confidence: 99%
“…As OA appears to diagnose and prognose joint disease progression over weeks or months, as opposed to years. In this regard, recent studies suggest the association of biomarkers, such as noncoding RNAs, 12 metabolites, 13 inflammatory markers, [14][15][16] and cartilage degradation products 17,18 with OA pathology (Figure 1), as well as other biomarker entities (e.g. epigenetic and microbial) reviewed in detail elsewhere.…”
Section: Introductionmentioning
confidence: 96%